Challenges for Inclusive Finance Expansion: the Case of CrediAmigo, a Brazilian MFI - Lavoie, Fréderic; Pozzebon, Marlei; Gonzalez, Lauro (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2011)
Investigating the replication of microcredit methodologies in Brazil, this paper seeks to explore the conditions under which microfinance and microcredit, two “financial inclusion” strategies, are likely to enhance social inclusion. A qualitative case study was conducted focusing the path of CrediAmigo, a Brazilian microfinance institution (MFI). This study is probably the first to provide an integrated perspective on critical issues concerning the replication of microcredit methodologies in Brazil. The findings may support MFI managers and policy makers in taking steps to facilitate the expansion of microfinance across Brazil.